Assessment of quality health information sources: comparative study between the citizen’s charthers of two unviersity hospitals (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
A citizen’s charter is an information dissemination tool and can be an effective tool in the healthcare field. This essay presents an ongoing study that aims to proposes to evaluate the quality of information in the citizen’s charters of two university hospitals, considering their effectiveness as health information sources and their alignment with SDG 3 of the 2030 Agenda. The research adopts a qualitative and comparative approach, focusing on the applicability of specific information quality criteria.
Keywords: quality of information; health information; health information sources; citizen’s charters